Trend Analysis of Tax Ratio as an Indicator of Tax Revenue Performance in Indonesia for the 2010–2024 Period - Anisa Nurfalah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The tax ratio is an important indicator for assessing a country’s tax revenue performance; however, in Indonesia it remains relatively low and volatile. This study analyzes the trend of the tax ratio in Indonesia over the period 2010–2024 and evaluates the stability of tax revenue performance within the context of macroeconomic dynamics. A quantitative descriptive approach is employed using secondary time-series data on tax revenue and Gross Domestic Product (GDP). The results indicate that the tax ratio ranged between 8.95% and 11.11%, showing a fluctuating pattern with a notable decline during 2016–2020 and a limited recovery in the post-pandemic period. These findings suggest that improvements in economic activity have not been fully reflected in tax revenue performance. Accordingly, stronger tax policies and administrative reforms are required to enhance the effectiveness and sustainability of revenue mobilization.